A Case of Reflection of Simple Wave From a Contact Discontinuity - Kononov, A.V. (Engineering Transactions, 1996)
An exact analytical solution is presented for the wave system describing a one-dimensional unsteady process of nonlinear reflection of an arbitrary simple wave from a contact discontinuity dividing two ideal perfect gases of constant values of adiabatic indices k and k0 which equal 3, and an arbitrary γ > 1, respectively. We suppose that the incident simple wave propagates through the gas of adiabatic index k equal to 3. As an example, we investigate the initial state of a one-dimensional process of expansion of condensed-phase products of detonation in a medium with counterpressure.